Audience Engagement Analysis of the Drama Cinta Sedalam Rindu through Uses and Gratification Theory - Nadya Fritanita Julyazti; Marcel Maulana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the motivation and audience engagement toward the television drama Cinta Sedalam Rindu through the Uses and Gratifications Theory approach. Produced by SinemArt and broadcast on SCTV, the series portrays themes of love and the struggles of young people in the digital era, successfully capturing the attention of both teenage and adult audiences. The research employs a qualitative descriptive approach using content analysis and social media observation techniques, encompassing platforms such as Instagram, TikTok, Twitter, and Facebook. The findings reveal that audiences actively use this drama to fulfill various needs: cognitive (gaining insight into life and social relationships), affective (expressing emotions and empathy), personal identity (reinforcing self-image through relatable characters), social integration (engaging with online communities and the cast), and diversion (escaping from daily routines and stress). Moreover, active audience participation on social media fosters a strong fan community and enhances emotional attachment to the content. These findings affirm that Cinta Sedalam Rindu serves not merely as a form of entertainment but also as a medium of social communication capable of shaping the audience's identity, emotions, and social relationships in the digital age.